The parameters of uncertainty in revenue law - Hingun, Mohsin; Safaradeen, Nafiu Olaitan (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Certainty in law is a much valued attribute and is fundamental to upholding the rule of law. In revenue law, tax payable must be certain and not arbitrary but can we interprete statutory provisions with certainty in the absence of important terms and concept purposely left out of the definition section. The problem is compounded by the wide discretionary powers given to tax officials in the execution of their functions. The lawyer’s definition of a term may not converge with definitions from other disciplines. A good example being the concept of profit but these disciplines may provide assistance; however the matter is resolved legally by examining the facts and applying the law as envisaged by Parliament. The essence of this contradiction underlines the difficulty in interpretation of language as used in the legislation by the legislators, which ultimately sheds light on the causes of uncertainty in law. However, uncertainty has a utilitarian role, leaving the courts latitude to find the appropriate legal solution, either in defining terminologies and concepts or in the application of legal rules as long as the courts approach is predictable.